2003
DOI: 10.1016/s0014-5793(02)03900-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cupin‐type phosphoglucose isomerase from the hyperthermophilic archaeon Thermococcus litoralisa

Abstract: The gene encoding phosphoglucose isomerase was cloned from Thermococcus litoralis, and functionally expressed in Escherichia coli. The puri¢ed enzyme, a homodimer of 21.5 kDa subunits, was biochemically characterized. The inhibition constants for four competitive inhibitors were determined. The enzyme contained 1.25 mol Fe and 0.24 mol Zn per dimer. The activity was enhanced by the addition of Fe , but inhibited by Zn 2+ and EDTA. Enzymes with mutations in conserved histidine and glutamate residues in their cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…Moreover, the plot of the Student-t-values over measurement points shows that in general as much data points as possible should be collected ( As already done in Section 2.3, these investigations were also performed using a uni-uni mechanism and a bi-bi mechanism. The parameter values for these studies were obtained from phosphoglucose isomerase (Jeong et al, 2003) and from formate dehydrogenase (Michalik et al, 2007). These studies confirm the observed trends (data not shown).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the plot of the Student-t-values over measurement points shows that in general as much data points as possible should be collected ( As already done in Section 2.3, these investigations were also performed using a uni-uni mechanism and a bi-bi mechanism. The parameter values for these studies were obtained from phosphoglucose isomerase (Jeong et al, 2003) and from formate dehydrogenase (Michalik et al, 2007). These studies confirm the observed trends (data not shown).…”
Section: Resultssupporting
confidence: 81%
“…The experimental data for these studies were obtained from industrially important enzymes − phosphoglucose isomerase (Jeong et al, 2003) and formate dehydrogenase (Michalik et al, 2007). Basically the same results were obtained.…”
Section: Error Caused By Steady-state Assumptionmentioning
confidence: 67%
“…putative homologs) are significantly smaller (296 -354 amino acids versus more than 401 amino acids (M. jannaschii for conventional PGIs (Table II; www.sanger.ac.uk/cgi-bin/Pfam)) and might represent the minimal core structure necessary for a phosphoglucose isomerase of the PGI superfamily. In contrast, the cupin type PGIs from Thermococcales have subunits of about 23 kDa and are significantly smaller (Table II) (2,28). In accordance with the optimal growth temperature of A. pernix, the hyperthermophilic ApPGI/PMI is the most thermophilic PGI and PMI described so far.…”
Section: Discussionmentioning
confidence: 76%
“…5). PGI from T. litoralis, which is highly similar to the enzyme from P. furiosus, contains iron with traces of zinc (3).…”
mentioning
confidence: 95%
“…In eubacteria, eukaryotes, and a few archaea, the enzyme is of the conventional type that has been studied extensively at the biochemical and structural level. To date, the second, novel type has been found in two Euryarchaeota species, Pyrococcus furiosus and Thermococcus litoralis (1)(2)(3). This is markedly smaller than conventional PGI; for instance, the enzyme from P. furiosus comprises a dimer of 43 kDa (1,2), whereas mammalian PGI is a 132-kDa dimer.…”
mentioning
confidence: 99%